2013
DOI: 10.1021/jp306793r
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Visible-Light Response of Nickel(II) Oxide Cluster Surface Modified Titanium(IV) Dioxide

Abstract: Access to the full text of the published version may require a subscription. states, whereas NiO cluster levels are generated near the conduction band minimum 22 of anatase. This is in contrast to the SnO 2 /rutile TiO 2 system, where the density of states near the conduction band minimum 23 increases with the VB unmodified. In the NiO/TiO 2 system, the band gaps of both rutile and anatase are narrowed by up to 0.8 24 eV compared with pristine TiO 2 , which pushes the photoactivity into the visible region. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 61 publications
8
69
0
Order By: Relevance
“…Other combined experimental and DFT studies on transition metal oxide modified TiO2 can be found in refs. [89][90][91] and will be discussed in Section 4. Reproduced from [78] , 2013, American Chemical Society For modification of rutile with a CuO nanocluster a new, empty Cu 3d state is present in the VB-CB gap, which arises from the presence of a Cu 2+ oxidation state, with a 3d 9 electronic configuration.…”
Section: Transition Metal Oxide Modified Tio2: Cuo and Feox Nanoclustmentioning
confidence: 99%
See 2 more Smart Citations
“…Other combined experimental and DFT studies on transition metal oxide modified TiO2 can be found in refs. [89][90][91] and will be discussed in Section 4. Reproduced from [78] , 2013, American Chemical Society For modification of rutile with a CuO nanocluster a new, empty Cu 3d state is present in the VB-CB gap, which arises from the presence of a Cu 2+ oxidation state, with a 3d 9 electronic configuration.…”
Section: Transition Metal Oxide Modified Tio2: Cuo and Feox Nanoclustmentioning
confidence: 99%
“…In experimental work from a number of groups [73,77,78,[89][90][91][92][93][94]102,103,[112][113][114][115][116][117] doped TiO2 system, we consider N-F co-doped TiO2 [118] which shows visible light absorption, but no photocurrent. The surface modification approach has the potential to alleviate some of these issues with doped TiO2.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…These properties make TiO 2 suitable as a photocatalyst for water-splitting technology using renewable resource in the form of solar light, 1,2 or for depollution of toxic organic 30 pollutants from the domestic and industry use. [3][4][5] However the band gap of TiO 2 which lies in the range of 3.0 to 3.2 eV (depending on the crystal form) can only absorb in the UV region.…”
mentioning
confidence: 99%
“…These new 30 states can function as states into which an electron from the (unmodified) TiO 2 valence band can be excited, thus giving an effectively reduced energy gap when compared to unmodified TiO 2 (again the surface VB-CB energy gap is unchanged upon modification). In this case, the energy gap underestimation with 35 DFT is clearly apparent, as in the largest Pb 4 O 8 nanocluster, the empty Pb states are found ca.…”
mentioning
confidence: 99%